Relationships between soil parameters and physiological status of Miscanthus x giganteus cultivated on soil contaminated with trace elements under NPK fertilisation vs. microbial inoculation. (June 2017) - Pogrzeba, Marta; Rusinowski, Szymon; Sitko, Krzysztof; Krzyżak, Jacek; Skalska, Aleksandra; Małkowski, Eugeniusz; Ciszek, Dorota; Werle, Sebastian; McCalmont, Jon Paul; Mos, Michal; Kalaji, Hazem M.
Abstract: Crop growth and development can be influenced by a range of parameters, soil health, cultivation and nutrient status all play a major role. Nutrient status of plants can be enhanced both through chemical fertiliser additions (e.g. N, P, K supplementation) or microbial fixation and mobilisation of naturally occurring nutrients. With current EU priorities discouraging the production of biomass on high quality soils there is a need to investigate the potential of more marginal soils to produce these feedstocks and the impacts of soil amendments on crop yields within them. This study investigated the potential for Miscanthus x giganteus to be grown in trace element (TE)-contaminated soils, ideally offering a mechanism to (phyto)manage these contaminated lands. Comprehensive surveys are needed to understand plant-soil interactions under these conditions. Here we studied the impacts of two fertiliser treatments on soil physico-chemical properties under Miscanthus x giganteus cultivated on Pb, Cd and Zn contaminated arable land. Results covered a range of parameters, including soil rhizosphere activity, arbuscular mycorrhization (AM), as well as plant physiological parameters associated with photosynthesis, TE leaf concentrations and growth performance. Fertilization increased growth and gas exchange capacity, enhanced rhizosphere microbial activity and increased Zn, Mg and N leaf concentration. Fertilization reduced root colonisation by AMF and caused higher chlorophyll concentration in plant leaves. Microbial inoculation seems to be a promising alternative for chemical fertilizers, especially due to an insignificant influence on the mobility of toxic trace elements (particularly Cd and Zn). Graphical abstract: Highlights: Relationships in plant-TEC soil system were investigated for Miscanthus x giganteus . Both types of fertilisers increased growth, gas exchange capacity and RMA of tested plants. Microbial inoculation seems to be good alternative for chemical fertilizers. Abstract : Fertilization increased growth and gas exchange parameters, rhizosphere microbial activity and leaf Zn, Mg and N concentrations of Miscanthus x giganteus .